Chemical Composition and Biological Activity of the Essential Oil of Origanum vulgare ssp. hirtum from Different Areas in the Southern Apennines (Italy). Issue 4 (April 2014) - Mancini, Emilia; Camele, Ippolito; Elshafie, Hazem S.; De Martino, Laura; Pellegrino, Carlo; Grulova, Daniela; De Feo, Vincenzo
Abstract The chemical composition of the essential oils of Origanum vulgare ssp. hirtum, growing wild in three different localities in the Southern Apennines, was studied by GC‐FID and GC/MS analyses. In total, 103 compounds were identified. The oils were mainly composed of phenolic compounds and all oils belonged to the chemotype carvacrol/thymol. The three essential oils were evaluated for their in vitro phytotoxic activity by determining their influence on the germination and initial radicle elongation of Sinapis arvensis L., Phalaris canariensis L., Lepidium sativum L., and Raphanus sativus L. The seed germination and radicle growth were affected in various degrees. Moreover, the antifungal activity of the three essential oils was assayed against three species causing pre‐ and postharvest fruit decay (Monilinia laxa, M. fructigena, and M. fructicola). At 1000 ppm, the three oils completely inhibited fungal growth. The hemolytic activity of the oils was assayed and showed no effect on the cell membranes of bovine erythrocytes.